MANAJEMEN STRATEGIS PENGEMBANGAN KAWASAN PARIWISATA SEHAT DI KOTA PAYAKUMBUH - Amril, Nadatul Khaira; SD, Zaili Rusli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Â Payakumbuh City has been awarded â€œHealthy Cityâ€ from 2004 to 2019. This Healthy City assessment consists of 9 areas, one of them is healthy tourism. The tourism sector is very potential to be developed, because Payakumbuh City has a strategic location. But in reality, problems are still found in the planning and implementation to realize healthy tourism in Payakumbuh. This study aims to determine strategic management to developing healthy tourism in Payakumbuh City, and the inhibiting factors in strategic management healthy tourism development in Payakumbuh City. The method used is a qualitative method with case study approach. The research information was determined by purposive sampling technique. Collecting data through observation, interviews and documentation and data analysis using qualitative descriptive methods. The research results show that the formulation, implementation and evaluation of the strategy was not maximum. The inhibiting factors for the strategic management to development of healthy tourism in Payakumbuh are inaccurate budget planning, lack of community participation and tourism organizations that have not been active. The results of this research found that the strategy for developing healthy tourism in Payakumbuh was not optimal.Keywords : Strategic Management, Development, Healthy TourismÂ